Sudha Murty…. A Coach From Childhood - Shushma Raj Choudhary (IJRDO - Journal of Social Science and Humanities Research, 2026)
Sudha Murty, born 19 August 1950 is an Indian educator, novelist, and humanitarian. She is the Founder-Chairperson of the non-profit charitable organization Infosys Foundation. She is married to the co-founder of Infosys, N. R. Narayana Murthy. Murty was nominated as Member of Parliament, Rajya Sabha on 8 March 2024 for her contribution to social work and education. Murty was awarded the Padma Shri, the fourth highest civilian award in India, for social work by the Government of India in 2006. In 2023, she was awarded the Padma Bhushan, the third highest civilian award in India. Sudha Murty began her professional career in computer science and engineering. She is a member of the public health care initiatives of the Gates Foundation. She has founded several orphanages, participated in rural development efforts, supported the movement to provide all Karnataka government schools with computer and library facilities, and established Murty Classical Library of India at Harvard University.